Recent Achievements of NEDO Durability Project with an Emphasis on Correlation Between Cathode Overpotential and Ohmic Loss1. Issue 4 (17th May 2017) - Yokokawa, H.; Hori, Y.; Shigehisa, T.; Suzuki, M.; Inoue, S.; Suto, T.; Tomida, K.; Shimazu, M.; Kawakami, A.; Sumi, H.; Ohmori, M.; Mori, N.; et al.
Abstract: Long‐term performance testes by CRIEPI (Central Research Institute for Electric Power Industry) on six industrial stacks have revealed an interesting correlation between cathode polarization loss and ohmic loss. To make clear the physicochemical meaning of this correlation, detailed analyses were made on the conductivity degradation of YSZ electrolyte in button cells and then on the ohmic losses in the industrial cells in terms of time constants which are determined from speed of the tetragonal transformation through the Y diffusion from the cubic phase to the tetragonal phase. In some cases, shorter time constants (faster degradations) were detected than those expected from the two‐time‐constant (with and without NiO reduction effects) model, suggesting that additional ohmic losses after subtracting the contribution from the tetragonal transformation must be caused from other sources such as cathode‐degradation inducing effects. Main cathode degradations can be ascribed to sulfur poisoning due to contamination in air in the CRIEPI test site. An important feature was extracted as this cathode degradations became more severe when the gadolinium‐doped ceria (GDC) interlayers were fabricated into dense film. Plausible mechanisms for cathode degradations were proposed based on the Sr/Co depletion on surface of lanthanum strontium cobalt ferrite (LSFC) in the active area. Peculiar cathode degradations found in stacks are interpreted in term of changes in surface concentration by reactions with sulfur oxide, electrochemical side reactions for water vapor emission or Sr volatilization, and diffusion of Sr/Co from inside LSCF.